Learning Together Why and How? - Banerjee, Nitin (JOURNAL OF INDIAN EDUCATION, 2010)
With the changing global scenerio of education and demand of mass participation for the all round development of the country as well as of the world. It has become imperative to re-focus and ensure participation of all sections of people in the schooling system, so that all sorts of working and capable people are available at the right place for engaging them in the developmental process. This is also one of the focused areas of Sarva Shiksha Abhiyan. (vide para1.4.9(d) Mission statement of SSA which reads as follows: “ An equity based approach that focuses on the needs of … children with special needs”). The concept of inclusion is not new but it will take time for our practicing teachers to adopt themselves to such situation and explore the merits of inclusive learning and Multigrade teaching. Although legal provisions are made (Article 21-A) so that education becomes one of the fundamental rights, but like many other behaviour laws, the right to education is yet to be percieved and enacted with full potential. International organisations and many NGOs are actively involved to look after the issue and address such neglected (gray) areas with proper training and study materials developed at the International levels. Still it is a question of attitudinal change and convinces us of the urgency of the situation and moulds ourselves accordingly.